Jealousy, sexism, and romantic love myths: the role of beliefs in online dating violence - Ramírez-Carrasco, Daniela; Ferrer-Urbina, Rodrigo; Ponce-Correa, Felipe (Frontiers in Psychology, 2023)
With the massification of the Internet and social networks, a new form of dating violence called cyber-violence has emerged, which involves behaviors of control, humiliation, intimidation and threats towards the partner or ex-partner. Using a non-probabilistic sample of 1,001 participants aged 18 to 25 years, the present study used an ex post facto, retrospective, cross-sectional, single-group design to analyze the joint effects that beliefs associated with dating violence such as romantic love myths, jealousy, and sexism have on the victimization and perpetration of cyber-violence. The results evidenced that jealousy is involved in both Cyber-victimization and Cyber-harassment perpetrated, while sexist beliefs are only involved in perpetration. In the discussion section, it is postulated that cyber-violence is a phenomenon that is more related to the probability of aggression, but not to the probability of being a victim. Finally, limitations and implications for future research are discussed.